PEMANFAATAN LIMBAH PLASTIK MENJADI KERAJINAN TANGAN BAGI IBU-IBU PKK DESA MEJASEM BARAT, KECAMATAN KERAMAT, KABUPATEN TEGAL - Mohammad Arridho Nur Amin Amin; Dewi Indriasih; Yuni Utami (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Tegal Regency is one of the regencies in Central Java Province which is located in the northwest. One of the sub-districts in Tegal Regency is Kramat District, in that district many residents only depend on their husbands for their needs, so PKK women take the initiative to make craft training from plastic waste, as well as realize the PKK basic program in preserving the environment, especially plastic waste. The method used in this community service activity is group-based as a medium of learning and mentoring, planning and monitoring. The number of participants who took part in this devotional activity was 15 people consisting of PKK women in West Mejasem Village. The result of this service is that the PKK women in West Mejasem Village have the knowledge and ability to develop skills in making decorative flowers from plastic waste, the decorations made are in the form of flowers which can later be sold and have more value when compared to plastic waste which is directly sold, It is hoped that with this training, the residents of West Jasem Village can have skills and become one of the other sources of income to increase their income.